METODE DAKWAH KEPADA PENGUASA (STUDI ANALISIS PENDEKATAN ETIKA DAKWAH) - Mastori Mastori (AL-FIKRA, 2018)
This article discusses the method of da'wah to the authorities. This paper is intended to provide information to Islamic leaders or Islamic activists about how to preach to the authorities, including through letters, criticizing openly or just denying the tyranny of the ruler.